(untitled) (Academia Science Repository, 2023)
In this article, computer science education is becoming increasingly important in modern society, since technology is now an integral part of almost all aspects of our life. There is a growing demand for education in Informatics in schools, colleges and universities around the world. However, traditional methods of teaching computer science may no longer be sufficient to meet the needs of modern students.